The Pathology of Hereditary Breast Cancer - Honrado, Emiliano (Hered Cancer Clin Pract, 2004)
Several studies have demonstrated that familial breast cancers associated with BRCA1 or BRCA2 germline mutations differ in their morphological and immunohistochemical characteristics. Cancers associated with BRCA1 are poorly differentiated infiltrating ductal carcinomas (IDCs) with higher mitotic counts and pleomorphism and less tubule formation than sporadic tumours. In addition, more cases with the morphological features of typical or atypical medullary carcinoma are seen in these patients. Breast carcinomas from BRCA2 mutation carriers tend to be of higher grade than sporadic age-matched controls. Regarding immunophenotypic features. BRCA1 tumours have been found to be more frequently oestrogen receptor- (ER) and progesterone receptor-(PR) negative, and p53-positive than age-matched controls, whereas these differences are not usually found in BRCA2-associated tumours. A higher frequency and unusual location of p53 mutations have been described in BRCA1/2 carcinomas. Furthermore, BRCA1- and BRCA2-associated breast carcinomas show a low frequency of HER-2 expression. Recent studies have shown that most BRCA1 carcinomas belong to the basal cell phenotype, a subtype of high grade, highly proliferating ER/HER2-negative breast carcinoma characterized by the expression of basal or myoepithelial markers, such as basal keratins, P-cadherin, EGFR, etc. This phenotype occurs with a higher incidence in BRCA1 tumours than in sporadic carcinomas and is rarely found in BRCA2 carcinomas. Hereditary carcinomas not attributable to BRCA1/2 mutations have phenotypic similarities with BRCA2 tumours, but tend to be of lesser grade and lower proliferation index. The pathological features of hereditary breast cancer can drive specific treatment and influence the process of mutation screening.